A hypertext environment for interacting with large textual databases - Agosti, M.; Gradenigo, G.; Marchetti, P.G. (Information processing & management, 1992)
This paper presents a design and implementation project based on a two-level conceptual architecture for the construction of a hypertext environment for interacting with large textual databases. The conceptual architecture has been proposed to be used for a semantic representation of the informative content of a collection of documents and for the organisation of the document collection itself. The hypertext environment is based on a set of functions that permits one to exploit the potential capabilities of the two-level architecture. Those functions are presented in detail. The paper reports some results of a more general project whose final goal is the definition of a new model for information retrieval: a model with information retrieval capabilities embedded within a hypertext environment. Finally, an outline is presented of the characteristics of a prototype, named HYPERLINE, of the hypertext environment. This prototype has been developed by the Information Retrieval Service of the European Space Agency (ESA-IRS).